Images on Social Media, Their Producers and Viewers (KULT_online, 2020)
The book Image Testimonies: Witnessing in Times of Social Media offers a comprehensive corpus of observations on different localities and experiences which tackle the continuous discussion over the role of testimony and witnessing through social media in times of civil upheaval. Topics included are different concepts of witnessing in relation to image testimonies, body and performativity, the role of the spectator, temporalities of witnessing and others. This is explored in a fascinating collection of essays, conversations, and artistic sketches.